Psycho-Cognitive Attitude Towards Mental Training & Its Relation to Locus of Control - Nadim Sh. Al-Wattar; Manhal Kh. Sultan (مجلة الرافدين للعلوم الرياضية, 2007)
Abstract The psycho-cognitive attitude is considered on of the basic elements through which the individual adopts a group of ideas and beliefs related to the subject of his attitudes assuming that the individual is motivated in his various performances to achieve cognitive balance and that the nature of his motivation predominates his performance and his interaction according to the encountered situation. The study aimed to investigate the following: • Constructing a scale for the psycho-cognitive attitude towards mental training of the population. • Expound the relation between psycho-cognitive attitude towards mental training and the locus of control of sport game coaches according to the attitudes towards internal and external control. The researchers postulated the following hypothesis • No significant correlation exists between psycho-cognitive attitude towards mental training and the locus of control of the population. The population consisted of (208) sport coaches of university sport directories distributed within (10) Iraqi universities namely the universities of (Mosul, Irbill, Duhok, Kuya (Sulaimania), Tikrit, Kirkuk, Diyala, Baghdad, Technology, and Al mustanssirya. ) The population sample was divided into two groups in order to construct and implement the psycho-cognitive scale devised by the researchers through number of scientific procedures. One hundred and seventy seven coaches representing of 85.8% of the population were selected to represent the investigated sample while (31) coaches representing 14.9% of the population were chosen as the implementation group. Thus, the researchers relayed on the stated percentages indicated in the ratio of representation of the descriptive population for the implementation. The researchers reached the following conclusions • A direct significant correlation exists between psycho-cognitive attitude towards mental training and the locus of control among the couches with internal control. The researchers recommend that more interest should be placed on psycho-cognitive attitude towards mental training which can be achieved through scientific and psychological courses aiming to expound the importance of mental training and its role to prepare the players in spot competitions.